2006
DOI: 10.2139/ssrn.891206
|View full text |Cite
|
Sign up to set email alerts
|

The Corporate Governance Role of the Media: Evidence from Russia

Abstract: We study the effect of media coverage on corporate governance by focusing on Russia in the period 1999-2002. This setting offers us three ideal conditions for such a study: plenty of corporate governance violations, no alternative mechanisms to address them, and the presence of an investment fund (the Hermitage) that actively lobbies the international press to shame companies perpetrating those violations. We find that Hermitage's lobbying is effective in increasing the coverage of corporate governance violati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
324
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(336 citation statements)
references
References 36 publications
(24 reference statements)
11
324
0
1
Order By: Relevance
“…Johnson et al (2005) have used newspapers as a data source and fall into this second category by studying the influence of the financial press on stockholder wealth. Media's role as a monitor for accounting fraud has been recently studied (Dyck et al, 2010;Miller, 2006) and has been shown to be important due to the pressure it places on management (Dyck et al, 2008). While we recognize that the media may have incentives to highlight fraudulent behavior to increase circulation, the press still fulfills two key roles.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson et al (2005) have used newspapers as a data source and fall into this second category by studying the influence of the financial press on stockholder wealth. Media's role as a monitor for accounting fraud has been recently studied (Dyck et al, 2010;Miller, 2006) and has been shown to be important due to the pressure it places on management (Dyck et al, 2008). While we recognize that the media may have incentives to highlight fraudulent behavior to increase circulation, the press still fulfills two key roles.…”
Section: Samplingmentioning
confidence: 99%
“…While we recognize that the media may have incentives to highlight fraudulent behavior to increase circulation, the press still fulfills two key roles. First, in relaying information from other intermediaries (auditors, analysts, lawsuits), the press attracts the attention of institutions that may take action (e.g., regulatory bodies, consumer groups, investment funds) (Dyck et al, 2008). Second, the press can produce new information through its own investigations and analysis.…”
Section: Samplingmentioning
confidence: 99%
“…News media are generally profit driven and they naturally prefer to report news that would attract public attention M. Jia et al (Dyck et al 2008). A negative report exposing a firm engaging in pollution activity is newsworthy because readers are interested in knowing more about an activity that affects their daily lives in very significant ways.…”
Section: Research Framework and Hypothesis Development Research Framementioning
confidence: 99%
“…The news media has an important effect on corporate business practices due to their dominant position as information intermediaries in our society (Bednar 2012;Core et al 2008) for stakeholders, who access information about firms primarily via news media (Bednar et al 2013;Dyck et al 2008;Pollock and Rindova 2003). Previous studies have supported the notion that media reports (e.g., coverage and tenor) influence various aspects of corporate business, including stock performance (Bhattacharya et al 2009), CEO compensation and dismissal (Core et al 2008), corporate acquisitions (Liu and McConnell 2013), financial fraud (Miller 2006), and strategic change (Bednar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation